Can Robots Replace a Living Person in Medicine? - Xolmurodova Xulkar Xoliyorovna; Saidova Kamola Ilhamjanovna (Genius Journals, 2021)
Various types of medical robots are already performing a wide range of tasks, but even in the future, when machines become more sophisticated, they can hardly be completely trusted to make important decisions. It seems that complex manipulations independently carried out by robotic devices will also be controlled by humans. Consider how robotic assistants affect the level of development of medicine
Keywords: Equipment; Facilities; Opportunity; Experience